2011
DOI: 10.1103/physrevb.84.195469
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic stability of PuO2surfaces: Influence of electronic correlations

Abstract: In this article, we performed accurate ab initio calculations in order to address the influence of electronic correlations on the surface stability of PuO 2 . Various terminations of the (100), (110), and (111) orientations were considered, among which some are polar. Standard density-functional theory (DFT), which is known to provide a poor description of the electronic structure of plutonium oxides, predicts an unexpected stabilization of the polar uncompensated terminations O 2 -(111) and Pu-(111). We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…A limited number of publications have investigated noncollinear contributions, [48][49][50] and collinear 1k AFM order is often used to model the electronic structure. 9,34,42,49,[51][52][53][54][55][56][57][58][59][60][61][62][63] The inclusion of spin-orbit interactions (SOI) 14 is often ignored, 34,46,48,[60][61][62]64 although a number of investigations have highlighted its importance. 33,48 This is mainly due to the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of publications have investigated noncollinear contributions, [48][49][50] and collinear 1k AFM order is often used to model the electronic structure. 9,34,42,49,[51][52][53][54][55][56][57][58][59][60][61][62][63] The inclusion of spin-orbit interactions (SOI) 14 is often ignored, 34,46,48,[60][61][62]64 although a number of investigations have highlighted its importance. 33,48 This is mainly due to the computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…The effective modification of pure DFT by LDA/GGA+U formalisms has been confirmed widely in studies of PuO 2 [27][28][29][30][31][32][33][34][35], which have reported the AFM-insulator ground state of…”
Section: Introductionmentioning
confidence: 98%
“…Calculated surface energies of AnO 2 have been reported in several papers, particularly for ThO 2 , UO 2 , and PuO 2 . Tables 1-3 summarize the surface energies for the low indexed (111), (110), and (100) surfaces, comparing the different reports that employed DFT and those that relied on other classical models [25][26][27][28][29][30][31][32][33]. It is seen that DFT calculations give rise to smaller surface energies than the classical models for ThO 2 , UO 2 , and PuO 2 surfaces.…”
Section: Introductionmentioning
confidence: 99%